Design of a SMS Based Voting System. - Owembabazi Justus (Kabale University, 2023)
A vote is a formal expression of an individual's choice in voting, an individual can vote for or against some motion or idea, for a candidate of choice or preference, a political party, any organization be it social or economic and so on. Uganda and many other African countries use the conventional voting system based on paper. This system is slow, expensive, less secure, not reliable, cumbersome and not very transparent. It is this background of study that has motivated the design of an Electronic voting system based voting using a GSM module, which is much reliable and cheaper hence saving a lot of resources. The project aims to design a cost effective, secure, less cumbersome and efficient SMS based voting system. Objectives of the project are to design a cost-effective and secure Electronic voting system based on GSM, to come up with an electronic design of the circuit and to test and troubleshoot for any flows. Related literature about the electronic voting was cited. The Waterfall project development method was used for this project. It is a stage by stage system and the advantage of this system is that it is possible to return to the previous stage or stages whenever a hiccup or error arises. The system began with designing using Multism and proteus soft wares. It was a well written code using the Arduino IDE was simulated, measured the output voltage, current and the output wave form displayed using the oscilloscope. Lastly a well-functioning system was obtained.